2018
DOI: 10.1038/s41598-018-34571-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coffee or coffee components on gut microbiome and short-chain fatty acids in a mouse model of metabolic syndrome

Abstract: We previously showed that male Tsumura Suzuki obese diabetes (TSOD) mice, a spontaneous mouse model of metabolic syndrome, manifested gut dysbiosis and subsequent disruption of the type and quantity of plasma short-chain fatty acids (SCFAs), and daily coffee intake prevented nonalcoholic steatohepatitis in this mouse model. Here, we present a preliminary study on whether coffee and its major components, caffeine and chlorogenic acid, would affect the gut dysbiosis and the disrupted plasma SCFA profile of TSOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 59 publications
1
46
1
2
Order By: Relevance
“…Caffeine is also a widely used ergogenic aid among athletes. Coffee, one of the primary dietary sources of caffeine, has been linked to increases in Bifidobacterium and protection against high-fat diet-induced decreases in Lactobacillus, though these effects may be due to other bioactive compounds present in coffee such as chlorogenic acid (119). The effect of these aspects of dietary intake on the gut microbiome in athletes is only one half of the story.…”
Section: Effects Of Supplements and Dietary Patterns On The Gut Micromentioning
confidence: 99%
“…Caffeine is also a widely used ergogenic aid among athletes. Coffee, one of the primary dietary sources of caffeine, has been linked to increases in Bifidobacterium and protection against high-fat diet-induced decreases in Lactobacillus, though these effects may be due to other bioactive compounds present in coffee such as chlorogenic acid (119). The effect of these aspects of dietary intake on the gut microbiome in athletes is only one half of the story.…”
Section: Effects Of Supplements and Dietary Patterns On The Gut Micromentioning
confidence: 99%
“…Coffee is one of the most popular beverages nowadays all over the world, with an annual global production of 10.4 × 10 6 tons and it plays an important cultural and economic role [1]. It contains more than 1500 chemical components, being responsible for sensorial and functional properties of the coffee beverage, the second most valuable legally traded commodity [2][3][4]. A recent study by Samoggia et al (2018) indicated that consumers' preferences for a specific coffee type mainly depended on sensory aspects like taste and aroma and functional motives to improve alertness and physical performance, beside habits and traditions of the consumer [5].…”
Section: Coffee As a Unique Beveragementioning
confidence: 99%
“…High consumption of sugars such as fructose, found in juices and carbonated drinks, can reduce the density of beneficial gut bacteria, as demonstrated in both animal and human studies [ 24 , 25 ]. Chronic caffeine consumption also alters the microbiome, although it is unknown to what extent these changes are beneficial or harmful [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%